AB0020 The Melanocortin System Is Responsive in Disease Driving Immune Cells in Rheumatoid Arthritis and May Offer A Pathway To Curative Treatment. (15th July 2016) - Andersen, M.; Meyer, M.K.; Nagaev, I.; Nagaeva, O.; WIkberg, J.E.S.; Mincheva-Nilsson, L.; Andersen, G.N.
Abstract : Background: Although biological agents may manage rheumatoid arthritis (RA), curative treatment is still the "holy grail". Induction of auto-antigen specific immune tolerance might offer a solution and obviate the need for life-long immunosuppression. Melanocortins are small peptides with considerable immune tolerance inducing, inflammation resolving and tissue preserving qualities (1). In animal experimental, autoimmune conditions, melanocortins have been demonstrated to bind differentially to melanocortin receptor (MCR) 1–5 on immune cells and to transform auto-reactive CD4 + T helper (Th) lymphocytes (ly) as well as sensitized CD8 + T cytotoxic (Tc) ly into regulatory T (Treg) ly and thus clear cell-mediated auto-immunity and delayed type hypersensitivity. In contrast to the situation in organ transplantation, clinical application of Treg therapy in human autoimmune disease is still non-existing, primarily because of a lack of in depth understanding. Objectives: To explore if the pro-resolving melanocortin system may offer a pathway to immune tolerance induction, we examined whether the melanocortin system is present and responsive in pathogenic immune cell subsets in RA. To this end, we related changes due to TNFα inhibition (I) in MCR1–5 mRNA levels to changes in Th1 signature-, inflammatory and regulatory cytokine mRNA levels. Methods: CD4 + Th, CD8 + Tc ly, CD19 + B-ly and CD14 + monocytes from seven patients with definite RA were isolated by Dynabeads before and three months after the start of TNFαI. Total RNA was extracted and mRNAs for MCR1–5 and a panel of disease driving Th1, inflammatory and regulatory cytokines were measured by real-time qRT-PCR. Fold changes in MCR1–5 gene levels were correlated to changes in cytokine gene levels. Results: MCR1–5 gene expressions were reduced in al examined cell types, significantly so in CD8 + Tc ly and CD19 + B ly in RA patients responding to TNFαI. In addition, Th1 and inflammatory cytokine mRNA levels were reduced in all cell types in responders. In a non-responding patient MCR1–5 gene expressions as well as Th1 and inflammatory cytokine gene levels increased substantially. The changes in MCR1–5 gene expressions in CD8 + Tc cells correlated significantly to changes in the Th1 cytokine IFNγ gene level in this cell type. Furthermore, we found significant correlations between changes in MCR 1, 3, 5- and change in IL-1β gene levels in CD4 + Th ly. Conclusions: Our results point at a responsive melanocortin system in immune cells in RA. Moreover, its regulation seems intimately connected to the disease driving Th1 response, that is IFNγ production by CD8 + Tc ly. Our results are underlined by the recently reported importance of IFNγ producing CD8 + Tc ly in early RA. Thus our findings indicate that the melanocortin pathway lies open to treatment of auto-reactive effector T ly from RA patients with MCR type specific synthetic ligands in vivo or in vitro to induce Treg transformation. Future curative induction of auto-antigen specific immune tolerance in RA may therefore involve the melanocortin system. References: Ahmed TJ, Montero-Melendez T, Peretti M, Pitzalis C. Curbing Inflammation through endogenous pathways: Focus on melanocortin peptides. Int J Inflamm 2013;2013:985815. Disclosure of Interest: None declared